Surgical treatment of posttraumatic deformations of the proximal femur - Lisunov, M. S.; Kozhemyaka, M. O.; Bohdan, O. V.; Лісунов, Михайло Сергійович; Кожем'яка, Максим Олександрович (My University, 2019)
Purpose of the research: Analyze the results of surgical treatment of post-traumatic deformations of the proximal femur using percutaneous intertrochanteric osteotomy with PFNA fixation.
Keywords: тези доповідей